DRUGS THAT AFFECT THE ACTIVITY OF THYROID HORMONES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The thyroid gland is one of the endocrine glands that plays an important role in the human body, and it participates in regulating the metabolic activity of the body. In recent years, drugs that affect the activity of this gland, their effectiveness and negative consequences, have been widely studied. The reason for choosing this topic is to deeply study the effect of thyroid hormones and drugs that affect them on the health of the body, to analyze current problems and scientific innovations in this regard.